2019
DOI: 10.1007/s10964-019-01097-w
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Discrimination and Suicidal Ideation in Emerging Adults: The Role of Traumatic Stress and Depressive Symptoms Varies by Gender not Race/Ethnicity

Abstract: Drawing from Race-Based Traumatic Stress theory, the present study examined whether traumatic stress and depressive symptoms differentially help explain the relation between racial/ethnic discrimination and suicidal ideation across gender and racial/ethnic groups. A racially/ethnically diverse group of emerging adults (N = 1344; M age = 19.88, SD = 2.25; 72% female; 46% Hispanic) completed a battery of self-report measures. A cross-sectional design was employed with a series of hierarchical linear regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 75 publications
(97 reference statements)
3
40
2
Order By: Relevance
“…A meta-analysis of studies based on nationally representative samples in the USA suggested that generally, females have a high risk of depression; however, the higher depression prevalence in females than in males was observed only in early adolescence and gradually disappeared in adulthood [ 21 ]. A US study [ 22 ] on 1344 college students aged 18–29 years (12% Asian) identified women are more likely to develop depressive symptoms (OR 1.99, 95%CI, 1.07–2.90). However, this difference between genders disappeared with suicidal ideation which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies based on nationally representative samples in the USA suggested that generally, females have a high risk of depression; however, the higher depression prevalence in females than in males was observed only in early adolescence and gradually disappeared in adulthood [ 21 ]. A US study [ 22 ] on 1344 college students aged 18–29 years (12% Asian) identified women are more likely to develop depressive symptoms (OR 1.99, 95%CI, 1.07–2.90). However, this difference between genders disappeared with suicidal ideation which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging adulthood is often characterized by elevated stress culminating in a heightened vulnerability to mental health concerns (Adkins et al, 2009;Ghobadzadeh et al, 2019;Lee & Dik, 2017). This vulnerability is compounded for racial minorities and those from low-income communities, given unique stressors (Diggs & Neppl, 2018;Polanco-Roman et al, 2019;Polanco-Roman & Miranda, 2013), who may be less likely to engage in mental health treatment seeking (Blumberg et al, 2015;Chandra et al, 2009;Cummings, 2014;National Institute of Mental Health, 2019;Parent et al, 2018). In the present sample, masculine status was associated with less depressive symptomology and more treatment seeking, especially for emerging adult men who were not depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Even more alarming are the effects of racial discrimination on the arousal system which can negatively impact stress regulation systems (Berger & Sarnyai, 2015). This finding reveals that traumatic stress through racial discrimination may be a pathway for increased risk for psychopathology, including suicidal behavior (Polanco-Roman et al, 2019). Race-related trauma stress has been conceptualized in the literature to be one of the leading causes for mental health symptoms among Black youth (Henderson et al, 2019).…”
Section: Risk Factorsmentioning
confidence: 99%